A directional look at F‐tests. Issue 4 (12th July 2019) - Mccormack, Andrew; Reid, Nancy; Sartori, Nicola; Theivendran, Sri‐Amirthan
Abstract : Directional testing of vector parameters, based on higher order approximations of likelihood theory, can ensure extremely accurate inference, even in high‐dimensional settings where standard first order likelihood results can perform poorly. Here we explore examples of directional inference where the calculations can be simplified, and prove that in several classical situations, the directional test reproduces exact results based on F ‐tests. These findings give a new interpretation of some classical results and support the use of directional testing in general models, where exact solutions are typically not available. The Canadian Journal of Statistics 47: 619–627; 2019 © 2019 Statistical Society of Canada Résumé : Les approximations d'ordre supérieur trouvées en théorie de la vraisemblance permettent de s'assurer d'une inférence très précise pour les tests directionnels sur les paramètres vecteurs, même dans les problèmes à haute dimension où la vraisemblance de premier ordre offre de mauvais résultats. Les auteurs explorent des exemples d'inférence directionnelle dont les calculs peuvent être simplifiés. Dans plusieurs cas classiques, ils prouvent que le test directionnel reproduit exactement les résultats de tests F, offrant une nouvelle interprétation de certains résultats classiques, et supportant l'usage d'un test directionnel en général, notamment lorsque aucune solution exacte n'est disponible. La revue canadienne de statistique 47: 619–627; 2019 © 2019 Société statistique du Canada